CHARACTERIZATION OF SPORE-FORMING BACTERIA ISOLATED FROM TILAPIA (OREOCHROMIS NILOTICUS) AND THEIR POTENTIAL FOR A PROBIOTIC CANDIDATE - Mawardi, Mira; Indrawati, Agustin; Lusiastuti, Angela Mariana; Wibawan, I Wayan Teguh (Indonesian Aquaculture Journal, 2023)
Gram-positive spore bacteria are widely used as probiotics in general sectors. However, there are still limited bacterial isolates as probiotic candidates available from indigenous isolates, especially in aquaculture. This study aimed to obtain potential spore-forming isolates as probiotic candidate for tilapia. Tilapia fish samples were collected from Sukabumi, Ciamis, Serang, and Papua. Bacterial isolates were isolated from the digestive tract of tilapia. Bacteria were identified based on their morphological, molecular characteristics, complete genome composition, and cell surface identification based on hydrophobic properties. In this study, six bacteria were isolated and identified by molecular characteristics using 16S rRNA sequences. Based on the phylogenetic analysis, the 9 PP isolate was Priestia megaterium basonym: Bacillus megaterium, CMS 16N isolate was Brevibacillus halotolerans, PPN 10 isolate was Bacillus sp., 3.1 SKBM isolate was Bacillus mycoides, CMS 22 N and SRG32 isolate were Bacillus subtilis. Six bacteria had different phenotypicals, ATGC sequence compositions, and a higher proportion of total G~C sequence composition above 50%. The coherent cell surface hydrophobicity test was positive on the SAT, SA, AA, and compact growth patterns in soft-agar media for 9 PP, CMS 22 N, and SRG32 isolates. From our study, the indigenous spore-forming bacteria isolated from tilapia stomachs are enzymatic bacteria, which have a strong attachment to host tissue and high potential as a probiotic candidate for fish. Various hydrophobicity test results from each isolate indicate that the protein composition in the cell surface is different.